Control of actin filament length by phosphorylation of fragmin-actin complex (The Rockefeller University Press, 1990)
Fragmin is a Ca2(+)-sensitive F-actin-severing protein purified from a slime mold, Physarum polycephalum (Hasegawa, T., S. Takahashi, H. Hayashi, and S. Hatano. 1980. Biochemistry. 19:2677-2683). It binds to G-actin to form a 1:1 fragmin/actin complex in the presence of micromolar free Ca2+. The complex nucleates actin polymerization and caps the barbed end of the short F-actin (Sugino, H., and S. Hatano. 1982. Cell Motil. 2:457-470). Subsequent removal of Ca2+, however, hardly dissociates the complex. This complex nucleates actin polymerization and caps the F-actin regardless of Ca2+ concentration. Here we report that this activity of fragmin-actin complex can be abolished by phosphorylation of actin of the complex. When crude extract from Physarum plasmodium was incubated with 5 mM ATP and 1 mM EGTA, the activities of the complex decreased to a great extent. The inactivation of the complex in the crude extract was not observed in the presence of Ca2+. In addition, the activities of the complex inactivated in the crude extract were restored under conditions suitable for phosphatase reactions. We purified factors that inactivated fragmin-actin complex from the crude extract. These factors phosphorylated actin of the complex, and the activities of the complex decreased with an increased level of phosphorylation of the complex. These factors, termed actin kinase, also inactivated the complex that capped the barbed end of short F-actin, leading to elongation of the short F-actin to long F-actin. Thus the length of F-actin can be controlled by phosphorylation of fragmin-actin complex by actin kinase.